Social support, parental role competence and satisfaction among Chinese mothers and fathers in the early postpartum period: A cross-sectional study. Issue 3 (May 2020) - Yang, Xiao; Ke, Sun; Gao, Ling-Ling
Abstract: Background: A sense of parental competence and satisfaction during the transition to parenthood can have a tremendous impact on the quality of parenting behaviors, with social support being an important facilitator. Aim: To examine parental role competence and satisfaction of Chinese mothers and fathers in the early postpartum period with regard to social support. Methods: A cross-sectional study was conducted in a regional teaching hospital in Guangzhou, China. The study was conducted between June 5 and November 16, 2015. One hundred and eighty parental pairs at 6–8 weeks after birth completed the Parenting Sense of Competence Scale, Perceived Social Support Scale, and socio-demographic questionnaires. Results: Parental role competence and satisfaction of Chinese mothers and fathers were at a moderate level, affected each other and there were no significant differences between the mothers and the fathers. The Competence Scale scores had a significant positive correlation with social support. Multiple regression analysis revealed two variables that predicted maternal Competence Scale scores: maternal social support and the paternal Competence Scale scores. Paternal social support and maternal Competence Scale scores contributed significantly to paternal Competence Scale scores. Conclusion: Parental role competence and satisfaction of mothers and fathers were at a moderate level and affected by the parenting partner. To improve parental role competence and satisfaction, health care professionals should develop strategies that impact the whole family and not just a single individual. Supportive parenting programs should be implemented for both mothers and fathers.